Communicating a Company’s CSR Activities Through Social Networks: A Theoretical Framework - Grzesiuk, Kalina (Annales. Etyka w Życiu Gospodarczym, 2018)
Companies which decide on socially responsible activities usually take into consideration benefits including the marketing effects of CSR programmes. However, in order to achieve that, the information about the socially responsible activities of companies must be spread and reach the audience of the company. That includes stakeholders related to the company that might be interested in receiving information about the social initiatives undertaken by the company. These stakeholders are connected with the firm through the network of social ties (SN). The main goal of this article is to present a theoretical framework of roles that these networks of social ties play in the effective communication of CSR activities. This paper is divided into three parts. The first one concerns the problem of how to communicate the involvement of a company in social initiatives. The second one contains the description of possible communication processes and strategies. The last one presents the analysis of the social networks perspective and its main characteristics and, in conclusion, it summarizes the main benefits a company can gain by applying the SN concept to CSR communication in the area of attribution and information spread through various channels.